Language for the school going deaf children - Mohamed Fazlulla K (Journal of All India Institute of Speech and Hearing, 1970)
In many states of the country the students have to study three languages intheir school curriculum. The languages became a great barrier for the deafchildren who try to be integrated in the schools for the normals. The problemgains in perspective when we remember that Language is the biggest problem forthe deaf child.